A little like magic - Kurpiel, Sarah (Rocky Pond Books, an imprint of Penguin Random House LLC, 2024)
"Our young narrator doesn't like itchy hats or cold wind, and she especially doesn't like going places she's never been before. But she reluctantly agrees to join her mom at an ice festival, where they watch sculptors chisel and drill until it's too cold to watch anymore. The next night, they return to see what the artists have created: sparkling, glorious sculptures that feel a little like magic. The ice art will stay with her long after it has melted away. This tender and lovely read-aloud is an exhilarating story of pushing past your comfort zone and finding inspiration in art and natural beauty." --